The Relationship between transformational leadership and job satisfaction Empirical Study of Police Force in Libya (Economic studies journal, 2021)
ABSTRACTThe purpose of this study quantitative cross-sectional research study was to determine the degree of the relationship between transformational leadership and job satisfaction in the Libyan police. The study was conducted to address the gap in the literature by providing a more detailed analysis of the extent to which the contribution of transformational leadership in the adoption of employee job satisfaction within a Libyan policing organization. The sample selected from 289 police forces. The population included the all Libyan police forces ranks, from Lance Corporal to Colonel. T-test and descriptive test showed that there is no bias response in between the responses provided by the participants. Regression analysis was used to test these hypotheses. The data for this study suggested that there was positive and significant relationship between Transformational leadership and the overall job satisfaction.  Recommendations for future research and practice are also provided.
Keywords: Transformational Leadership; Job Satisfaction and Libyan Police